Puncture wounds by driftwood catfish during bucket baths: Local habits of riverside people and fish natural history in the Amazon - Sazima, Ivan; Zuanon, Jansen; Haddad Júnior, Vidal [UNESP] (SAGE Publications, 2005)
Objective. - To assess the prevalence of stings by small spiny driftwood catfish (carataí) of the genus Centromochlus (Auchenipteridae) accidentally caught in buckets during bucket bathing by riverside people along the Brazilian Amazon and to determine the probability of catching specimens of these fish during random throws of a bucket into the river. Methods. - We interviewed 27 adult residents living at the confluence of the Negro and Solimões rivers in Brazil regarding whether or not they had ever been stung by driftwood catfish while bucket bathing. To assess the likelihood of catching catfish in bathing buckets, we randomly threw a typical plastic bucket used for bathing in 4 series of 10 throws into the river at dusk or night around a floating house. Results. - Seventeen of the 27 subjects (63%) reported being injured by driftwood catfish during bucket bathing. Three individuals (17.6%) had been injured 2 to 3 times, totaling 23 puncture accidents. All stings occurred at dusk or early night. In the 4 series of 10 bucket throws, we caught 3 driftwood catfish (in 1 series we did not catch any fish). Thus, the chance of catching a driftwood catfish in a single bucket throw at dusk was slightly less than 10%. Conclusions. - The prevalence of stings by driftwood catfish to people bucket bathing in this section of the Brazilian Amazon is high, partly because of the relatively high chances of catching these small catfish during random throws of a bathing bucket into the river.
Keywords: Bathing; Catfish; Centromochlus; Dangerous fish; Puncture wounds; Schooling habits; adult; bath; Brazil; catfish; Centromochlus heckelii; clinical article; controlled study; female; human; male; prevalence; river; wound; Adult; Animals; Baths; Behavior, Animal; Bites and Stings; Catfishes; Female; Humans; Male; Middle Aged; Wounds and Injuries